Chimeric Antigen Receptors; Their Current and Futuristic Scope - Sharma, Preeti; Kumar, Pradeep; Sharma, Rachna (Current Signal Transduction Therapy, 2018)
Crossing the threshold in clinical activity, chimeric antigen receptor-modified T cells have emerged as a new effective therapeutic regimen against various types of cancer both in adults and pediatric oncology. Currently available CARs are designed in a manner so that that they are capable of recognizing MHC independent antigen and incorporate costimulatory signal, converting the transduced T cells with potent activity. They have higher efficacy than monoclonal antibody and antibody-drug conjugate. There are various generations of CAR-T cells depending upon intracellular signalling domain number. CAR therapy maintained especial status as cancer immunotherapeutic agent, after targeting the CD19 cell surface molecules expressed in various types of cancers and are successfully transforming into clinic practice. Standing on the pillars of genetic engineering, T cell biology, molecular biology, tumor biology, target identification, CAR-T therapy holds great promise as off the shelf cancer therapeutic agent. Several unresolved concerns are still prevailing. Various issues with regard to safety, efficacy and their preparation, quality control issues, are still hampering our way. Cytokine release syndrome, neurological toxicities are few major side effects of the therapy blocking the successful development of CAR-T cells in the clinical trials. Aim: Current review is dealing with structural aspects of CAR T cells, target and signalling, their toxicity perspectives and current status and futuristic scope. Method: By undertaking structured search approach, we had gone through various bibliographic databases for peer-reviewed research literature on the focused research topic. Results: The review identifies various issues with regard to safety, efficacy and their preparation, structural aspects of CAR T cells, target and signalling, their toxicity perspectives and current status and futuristic scope. Conclusion: Amongst the most novel approaches, the CAR based research should be focussed on effective tumor targeting with limited toxicity in normal tissues, to improve efficacy with modulation of cell products or host cell products for rapid in vivo expansion.
Keywords: living drugs